Pengembangan E-Marketplace Terkoneksi Aplikasi Whatsapp Pada Pasar Muslim Info Kajian Purwokerto (IKP) - Eva Argarini Pratama; Corie Mei Hellyana; Sutrisno Sutrisno (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Whatsapp is an application that is popularly used today. By using Whatsapp someone can communicate with someone or several people at once (group). Not only communicating about personal or work, the use of WhatsApp (group) itself can now also be used as a medium of commerce. E-marketplace is also one of the trading media that has a wide range of facilities, including chat facilities on the e-marketplace. However, the existing chat facilities in some examples of e-marketplaces such as Tokopedia, Bukalapak, and Shopee require e-commerce users to install applications on their smartphone devices, thereby reducing memory space which results in reduced smartphone usage facilities. The Pasar Muslim whatsapp group consists of several groups that accommodate many members either as sellers or buyers. Requires a larger container (e-marketplace) to accommodate the number of members so that the marketing of the products sold by the seller is even wider and not only limited inside. group members only. Seeing the deficiencies that exist in each application, it is necessary to make a connection between these applications so that they can complement and meet the needs of IKP Muslim Market members. For this reason, an e-marketplace was developed according to the needs described earlier, while in the development of this e-marketplace using the waterfall method, this method provides a sequential software life-flow approach, starting from communication, planning, modeling, construction, & deployment.